A rapid one-step electrodeposition process for fabrication of superhydrobic surfaces on anode and cathode - Hao, Li-mei; Yan, Xiao-le; Xie, You; Zhang, Tao; Chen, Zhi (Journal of Central South University, 2016)
This work presents a method to solve the weak solubility of zinc chloride (ZnCl 2 ) in the ethanol by adding some reasonable water into an ethanol electrolyte containing ZnCl 2 and myristic acid (CH 3 (CH 2 ) 12 COOH). A rapid one-step electrodeposition process was developed to fabricate anodic (2.5 min) and cathodic (40 s) superhydrophobic surfaces of copper substrate (contact angle more than 150°) in an aqueous ethanol electrolyte. Morphology, composition, chemical structure and superhydrophobicity of these superhydrophobic surfaces were investigated by SEM, FTIR, XRD, and contact angle measurement, respectively. The results indicate that water ratio of the electrolyte can reduce the required deposition time, superhydrophobic surface needs over 30 min with anhydrous electrolyte, while it needs only 2.5 min with electrolyte including 10 mL water, and the maximum contact angle of anodic surface is 166° and that of the cathodic surface is 168°. Two copper electrode surfaces have different reactions in the process of electrodeposition time, and the anodic copper surface covers copper myristate (Cu[CH 3 (CH 2 ) 12 COO] 2 ) and cupric chloride (CuCl); while, zinc myristate (Zn[CH 3 (CH 2 ) 12 COO] 2 ) and pure zinc (Zn) appear on the cathodic surface.